Lewis & Clark : voyage of discovery - Ambrose, Stephen E.; Abell, Sam. ([Washington, D.C.] : National Geographic Society, 1998)
"Interweaves choice entries from the explorers' journals with the author's own latter-day chronicle of how he and his family continue to discover the Trail today."--Jacket.
Getting under way: August 1802-May 1804 -- Up the Missouri: May 1804-April 1805 -- Uncharted territory: April-August 1805 -- Most terrible mountains: August-October 1805 -- To the Pacific: October 1805-March 1806 -- Return home: March-December 1806.
Includes bibliographical references (page 254) and index.
Keywords: West (U.S.) -- Discovery and exploration; West (U.S.) -- Pictorial works; West (U.S.) -- Description and travel; Ambrose, Stephen E. -- Travel -- West (U. S.); Ambrose, Stephen E; Discoveries in geography; Travel; United States, West; Pictorial works